REALIZATION OF IDEA OF CIVIL SOCIETY IN THE CONSTITUTIONAL MEASUREMENT - Dmitry Anatolyevich Smirnov; Konstantin Aleksandrovich Strus (Вестник Северо-Кавказского федерального университета)
In article the main modern ideas of civil society reveal, its signs structure are defined. Social measure- ment of activity of civil society in modern Russia and foreign practice is considered. Need of adoption of the constitution of civil society is designated, the structure of the section devoted to civil society is offered.